As práticas de agricultura urbana como estratégia de garantia da segurança alimentar e da geração de renda no município de Pirapozinho/SP - Mendes, Daiara Batista [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The main objective of this work is to understand the different individual and / or institutional (collective) practices of urban agriculture in the municipality of Pirapozinho and their contributions in relation to food security and nutritional and the income generation for the population inserted in their production . In order to reach this goal, we return to an analysis of this practice in the municipality from a combination of the theoretical contribution acquired during the execution of this research and the results obtained in the field research, through the interviews with the public agents linked to the agricultural activities in the municipality and with urban agriculture practitioners and those responsible for institutions that develop urban agricultural practices with specific objectives, according to their target audience. In this sense, it was observed that, from the point of view of governmental actions, although urban agriculture is a recurrent activity in the daily life of the municipality, its producers are dispersed, without any collective organization through associations or unions representing them, precisely because they do not have any type of visibility on the part of the actions of the local administration. Concerning the dynamics of urban agriculture in the municipality, we find a practice aimed at self-consumption and income supplementation, being developed mainly by retirees and other residents who demonstrate their concern about household food security. We also analyze the important therapeutic and educational potential of collective practices developed in different institutions of the municipality

O presente trabalho tem como objetivo principal compreender as diferentes práticas individuais e/ou institucionais (coletivas) de agricultura urbana no município de Pirapozinho e as suas contribuições no que tange à segurança alimentar e nutricional e à geração de renda para a população inserida em sua produção. Para atingir tal finalidade, nos voltamos à uma análise dessa prática no município a partir de uma combinação entre o aporte teórico adquirido durante a execução desta pesquisa e os resultados obtidos nas pesquisas de campo, através das entrevistas com os agentes públicos ligados às atividades agrícolas no município e com os praticantes de agricultura urbana e os responsáveis por instituições que desenvolvem práticas agrícolas urbanas com objetivos específicos, de acordo com o seu público alvo. Nesse sentido, constatou-se que, do ponto de vista das ações governamentais, embora a agricultura urbana seja uma atividade recorrente no cotidiano do município, seus produtores encontram-se dispersos, sem nenhuma organização coletiva por meio de associações ou sindicatos que os represente, justamente pelo fato de não terem nenhum tipo de visibilidade por parte das ações da administração local. No que concerne à dinâmica da agricultura urbana no município, encontramos uma prática voltada para o autoconsumo e a complementação da renda, sendo desenvolvida, principalmente, por aposentados e demais moradores que demonstram a sua preocupação com a segurança alimentar das famílias. Analisamos também o importante potencial terapêutico e educacional das práticas coletivas desenvolvidas em diferentes instituições do município
Keywords: Geografia; Agricultura urbana; Segurança alimentar; Renda; Agricultura urbana - Pirapozinho (SP); Geografia agrícola; Geography